Strategy Increasing Entrepreneurship Interest to Post Migrant Workers through Training and Giving of Capital - Busro, Muhammad (International Research Journal of Business Studies, 2017)
This study aims to describe: the influence of coaching and giving capital disbursement to the interest of entrepreneurship of post migrant workers. The research method used is the method of action research, where the researcher gives treatment to the respondent in the form of assistance and the provision of soft capital by cooperating with the owner of the corporate social responsibility fund, i.e. the company around the research location, and ask the opinion of former migrant workers trained through instruments that have been prepared. The research was conducted in Lampung Province, on May-August 2016. Based on the result of the research, it can be concluded that, 1) the provision of entrepreneurship training can increase the entrepreneurship interest of post migrant workers in Lampung. Provision of coaching should be done continuously. 2) the provision of soft capital is also able to increase the entrepreneurial interest of post migrant workers in Lampung, the more soft capital is channeled to full-time workers. Although the capital provided is small, but able to pump their spirits to start a business.